Solid‐phase microextraction with fast GC combined with a high‐speed triple quadrupole mass spectrometer for targeted and untargeted food analysis. Issue 13 (7th June 2013) - Tranchida, Peter Quinto; Zoccali, Mariosimone; Schipilliti, Luisa; Sciarrone, Danilo; Dugo, Paola; Mondello, Luigi
Abstract : The present contribution is focused on the evaluation of a high‐speed triple quadrupole mass spectrometer, carried out under moderately fast GC conditions (analysis time: 16.6 min). The mass spectrometric instrument can be operated under high‐speed GC conditions, in both full‐scan (maximum scan speed: 20 000 amu/s) and multiple reaction monitoring (MRM) modes (minimum dwell time: 0.01 s). Additionally, the mass spectrometric system can generate full scan and MRM information, simultaneously and rapidly. A headspace solid‐phase microextraction with fast GC coupled to triple quadrupole MS approach was developed for the: (i) qualitative untargeted analysis of brewed tea volatiles, and (ii) MRM qualitative and quantitative analysis of targeted volatiles (also in brewed tea), namely 30 phytosanitary contaminants. The performance of the triple quadrupole instrument was satisfactory both for identification and quantification purposes. Furthermore, the method sensitivity was more than sufficient for the requirements of current legislation. Method validation, related to the MRM analysis, was performed considering: precision of quantification data (maximum coefficient of variation value: 12.0%) and quantification/qualification ion ratios (maximum coefficient of variation value: 14.4%), along with limits of detection (4 parts per trillion–5 parts per billion range) and quantification (14 parts per trillion–16 parts per billion range).